2019
DOI: 10.1039/c9sm01025d
|View full text |Cite
|
Sign up to set email alerts
|

Stable-streamlined cavities following the impact of non-superhydrophobic spheres on water

Abstract: Demonstrated is a stable-streamlined cavity attached to a hydrophilic sphere free-falling in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 48 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…Finally, we want to once more clarify that water–air interface mobility does not depend only on the water purity and the presence of surfactants but is also a strong function of the hydrodynamic regime and related shear rates. Smaller and slow moving bubbles are much easier to immobilize compared to larger bubbles subject to higher shear rates. Accordingly, all results for the water–air interface mobility discussed here should be considered in the context of the present experiments, which consist of millimeter-sized free-rising bubbles colliding with water–air interfaces.…”
Section: Results and Dicussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Finally, we want to once more clarify that water–air interface mobility does not depend only on the water purity and the presence of surfactants but is also a strong function of the hydrodynamic regime and related shear rates. Smaller and slow moving bubbles are much easier to immobilize compared to larger bubbles subject to higher shear rates. Accordingly, all results for the water–air interface mobility discussed here should be considered in the context of the present experiments, which consist of millimeter-sized free-rising bubbles colliding with water–air interfaces.…”
Section: Results and Dicussionmentioning
confidence: 90%
“…15 However, larger bubbles (of millimeter size) are shown to rise as a tangentially mobile interface if no added surfactant is present in the water. 19−22 Finally, for macroscopic bubbles and high shear rates as in foam shear experiments 23 or in the free-fall of centimeter-sized spheres with attached air cavities, 24,25 the bubble interface can be mobile even when a high concentration of low-modulus surfactants is present in the water.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other type is the passive method to retain the gas layer by a superhydrophobic coating. The immersed superhydrophobic surface can inherently stabilize the underwater gas film by entrapping gas pockets among the micro–nanostructure to form a “Cassie” state. However, the gas pockets are gradually disrupted by the surrounding shear flow, leading to an unwanted drag increase. Moreover, the micro–nanostructure on the superhydrophobic coating is fragile, and the coating-based method is currently limited due to its high cost, easy corrosion, and sensitive to abrasive conditions. Consequently, a feasible, robust, and universal strategy to stabilize the underwater gas–liquid interface without an external energy input remains extremely challenging.…”
Section: Introductionmentioning
confidence: 99%
“…As research goes on, CXCL1 has been identified to be intimately associated with the development of various cancers. For instance, Chengcheng Yang et al (16) found that CXCL1 could induce activation of ERK/MMP2/9 signaling axis to stimulate cell migration and invasion of ER-negative breast cancer. Lu Y et al (17) indicated that CXCL1-LCN2 axis is able to positively function on the development of prostate cancer via boosting Src signaling pathway activation as well as epithelial-mesenchymal transition process.…”
Section: Introductionmentioning
confidence: 99%